Clinical audit of dose-escalated radical radiotherapy for advanced cervical carcinoma using a pragmatic protocol (3 fractions of 8 Gy HDR brachytherapy) - Goswami, Jyotirup (Gynecol Oncol Rep, 2021)
INTRODUCTION: Recent image-guided brachytherapy data suggests, dose-escalation to a cumulative EQD2 (equivalent dose delivered at 2 Gy/#) of ≥87 Gy is associated with significantly better disease control. We present a clinical audit of a pragmatic radical radiotherapy protocol for advanced cervical cancer, using fewer fractions of brachytherapy than in the presently most popular protocol. MATERIAL & METHODS: Between July 2015 and December 2018, 96 consecutive advanced cervical carcinoma patients were treated by pelvic external beam radiotherapy (EBRT) (50 Gy/25fractions/5 weeks) ± weekly intravenous chemotherapy followed by image guided high dose rate (HDR) brachytherapy, using intracavitary/interstitial/hybrid techniques (intended point A dose: 8 Gy/fractions) × 3 fractions (cumulative target EQD2 ≥ 86 Gy). Insertion was done individually for each fraction of treatment. RESULTS: All patients completed their intended radiation protocol. 93.8% patients achieved complete response, while 6.2% patients achieved only partial response; no patients had stable/progressive disease. Out of the patients with partial response, 4.2% (4 out of 5 cases) cases of central/nodal residual disease underwent salvage surgery. At a median follow up of 21 months, 8.3% (8) patients had local failure, 1.1% (1) had nodal failure and 3.1% (3) had distant failures. Median Failure Free Survival was 29 months (26.5–31.5 months). On follow up, 6.3% and 3.2% patients had grade 2 or worse rectal and bladder morbidities respectively. CONCLUSION: The protocol under study has been safe and effective in achieving dose-escalated radical chemoradiation in advanced cervical carcinoma. The use of fewer insertions of brachytherapy is logistically easier & can also be expected to improve compliance.